Advances in imaging ultrastructure yield new insights into presynaptic biology - Bruckner, Joseph J.; Zhan, Hong; O’Connor-Giles, Kate M. (Frontiers in Cellular Neuroscience, 2015)
Synapses are the fundamental functional units of neural circuits, and their dysregulation has been implicated in diverse neurological disorders. At presynaptic terminals, neurotransmitter-filled synaptic vesicles are released in response to calcium influx through voltage-gated calcium channels activated by the arrival of an action potential. Decades of electrophysiological, biochemical, and genetic studies have contributed to a growing understanding of presynaptic biology. Imaging studies are yielding new insights into how synapses are organized to carry out their critical functions. The development of techniques for rapid immobilization and preservation of neuronal tissues for electron microscopy has led to a new renaissance in ultrastructural imaging that is rapidly advancing our understanding of synapse structure and function.